Quantifying the impact of mass vaccination programmes on notified cases in the Netherlands. Issue 6 (14th March 2018) - van Wijhe, M.; Tulen, A. D.; Korthals Altes, H.; McDonald, S. A.; de Melker, H. E.; Postma, M. J.; Wallinga, J.
Abstract: Vaccination programmes are considered a main contributor to the decline of infectious diseases over the 20th century. In recent years, the national vaccination coverage in the Netherlands has been declining, highlighting the need for continuous monitoring and evaluation of vaccination programmes. Our aim was to quantify the impact of long-standing vaccination programmes on notified cases in the Netherlands. We collected and digitised previously unavailable monthly case notifications of diphtheria, poliomyelitis, mumps and rubella in the Netherlands over the period 1919–2015. Poisson regression models accounting for seasonality, multi-year cycles, secular trends and auto-correlation were fit to pre-vaccination periods. Cases averted were calculated as the difference between observed and expected cases based on model projections. In the first 13 years of mass vaccinations, case notifications declined rapidly with 82.4% (95% credible interval (CI): 74.9–87.6) of notified cases of diphtheria averted, 92.9% (95% CI 85.0–97.2) cases of poliomyelitis, and 79.1% (95% CI 67.1–87.4) cases of mumps. Vaccination of 11-year-old girls against rubella averted 49.9% (95% CI 9.3–73.5) of cases, while universal vaccination averted 68.1% (95% CI 19.4–87.3) of cases. These findings show that vaccination programmes have contributed substantially to the reduction of infectious diseases in the Netherlands.